Projections of Temperature-Attributable Deaths in Portuguese Metropolitan Areas: A Time-Series Modelling Approach - Rodrigues, Mónica (2019)
Climate change is now widely recognised as the greatest global threat over the coming decades. This study aimed to quantify and project the effects of climate change on future temperature-attributable mortality due to circulatory system diseases (CSD) in Lisbon metropolitan area (LMA) and in Porto metropolitan area (PMA). The future time slices of Representative Concentration Pathway (RCP 8.5), mid-term (2046–2065) and long-term (2080–2099) were compared with the reference period (1986–2005). There is a significant decreasing trend in proportion to the overall extreme cold temperature-attributable mortality due to CSD in the future periods (2045–2065 and 2081–2099) in LMA, 0.63% and 0.73%, respectively, and in PMA, 0.62% for 2045–2065 and 0.69% for 2081–2099, compared to the historical period. The fraction attributable to extreme hot temperature in the summer months increased by 0.08% and 0.23%, from 0.04% in the historical period to 0.11% during 2046–2065, and to 0.27% during 2081–2099 in LMA. While there were no noticeable changes due to extreme hot temperature during the summer in PMA, significant increases were observed with warmer winter temperatures: 1.27% and 2.80%. The projections of future temperature-attributable mortality may provide valuable information to support climate policy decision making and temperature-related risk management.